Vulnerability to natural hazards of households in the coastal Barangays of New Washington, Aklan. - Bulacan, Nirvana Dominique F.; Carillo, Shelica Cheyene T. (2015.)
Natural phenomena such as typhoon, flood, storm surge, sea level rise and coastal erosion are some of the natural hazards that effect the world especially the coastal inhabitants. In line with this, coastal inhabitants are considered the most vulnerable to natural hazards. This study explores the vulnerability6 and socio-economic factors affecting it. This study aims to determine the extent of vulnerability to natural hazards of households in coastal barangays of New Washington, Aklan. Vulnerability Index (VI) was used to measure vulnerability in terms of natural hazard exposure, sensitivity and adaptive capacity. While, vulnerability as Expected Poverty (VEP) was used to determine socioeconomic factors that may affect vulnerability. The IV results to low vulnerability of households. Whereas, VEP determined some socio-economic factors that statistically affect vulnerability in terms of per capita consumption expenditure such as highest educational attainment and employment in agriculture or industry of the household head, land ownership, number of family members and income per capita.
Research Paper (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Households -- Coastal Barangays